Lobe of origin in the attribution of lung cancer to asbestos. Issue 8 (August 1988) - Weiss, W
Abstract : Lung cancer originates most commonly in the upper lobes in the general population but among workers with asbestosis it is most common in the lower lobes. Published data on lobar distribution were used to estimate the probabilities that lung cancer among asbestos workers is attributable to exposure to asbestos. This attribution varies directly with the relative risk. Critical values of the relative risk at which attribution of lung cancer to asbestos equalled its attribution to other causes, mainly smoking, were calculated. At a relative risk above 2.81 upper lobe cancers were more likely to be due to asbestos than not. For middle and lower lobe cancers, the critical relative risk was 1.55. These critical values were compared with published standardised mortality ratios reported for cohorts of workers with asbestosis. Since the ratios ranged from 6.3 to 9.1, the probability that lung cancer in such cases is due to asbestos is high regardless of lobe of origin. In many cohorts unstratified by the presence or absence of asbestosis the risk ratios are below one or both of these critical values. Since risk ratios are so high among workers with asbestosis, the ratios must be lower for workers without asbestosis than the overall ratios for unstratified cohorts. Therefore, the critical values may be useful in workers without asbestosis among such cohorts to estimate the upper limit of the probability that lung cancer in a given lobe is due to exposure to asbestos.